2015
DOI: 10.1002/cncr.29630
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of acupuncture to control hot flashes in cancer patients

Abstract: Hot flashes (HFs) are a common side effect of cancer treatment. The purpose of this systematic review was to evaluate evidence related to the use of acupuncture for HFs in cancer patients. EMBASE, MEDLINE, Cochrane (all databases), PubMed, the Cumulative Index to Nursing and Allied Health Literature, and Scopus were searched from their inception through December 2014. Included studies had to be randomized controlled trials with a usual-care and/or placebo comparison group that investigated acupuncture to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…In contrast with the recent RCTs, the current level of evidence from a series of meta-analyses is insufficient to suggest that acupuncture is an effective treatment for postoperative treatment-related side effects and hormone therapy–related psychosomatic events in patients with breast cancer. 15 , 29 - 32 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the recent RCTs, the current level of evidence from a series of meta-analyses is insufficient to suggest that acupuncture is an effective treatment for postoperative treatment-related side effects and hormone therapy–related psychosomatic events in patients with breast cancer. 15 , 29 - 32 …”
Section: Discussionmentioning
confidence: 99%
“…In an effort to synthesize evidence related to the use of acupuncture for symptom management in cancer patients, we have conducted multiple systematic reviews. 7 - 9 Symptoms for which acupuncture was found to be used most commonly include nausea/vomiting, pain, xerostomia (dry mouth), prolonged postoperative ileus, hot flashes, fatigue, sleep disturbances, mood changes, and peripheral neuropathy. Other symptoms of interest in patients treated in the IMC include shortness of breath and loss of appetite.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that acupuncture could significantly reduce pain, dysfunction, and xerostomia in cancer patients with a history of neck dissection. 21 Garcia et al 22 , 23 from the University of Texas MD Anderson Cancer Center has published systematic reviews on acupuncture in cancer care and control of hot flashes. Clinical data from his research suggested that patients who received inpatient acupuncture at a major cancer center experienced significant improvement in pain, sleep disturbance, anxiety, drowsiness, nausea, and fatigue.…”
Section: Discussionmentioning
confidence: 99%